Experiences of nursing students on simulative learning practice: a qualitative study - Aung, Khin Thandar; Ramli, Fazila (2018)
For nursing students, the way of learning is important because the nature of nursing education is not only depends on theory but also involves practical part that needs to handle the patients with sound clinical judgment and decision making skills. Moreover, students’ performances in clinical settings are also influenced by the ways of learning. The ways they are exposed to the real situations make them more knowledgeable and skilful. Therefore, simulative learning practice was introduced in many nursing institutions as one of the alternative ways to expose students to the practical skills. However, there is still little research done to investigate on understanding the experiences of nursing students regarding the simulative learning practice. Hence, this research aimed to explore the experiences of nursing students on simulative learning practice in International Islamic University, Malaysia (IIUM) at Kuantan, Pahang. A qualitative, phenomenological approach was carried out in February to April, 2017 using a purposive sampling method. Ten nursing students who have been experienced in the simulation were selected as study participants. As the study findings, participants reported that simulation helped them to give exposure and experience the situation that can mimic real condition, and also gained confidence in practical skills. However, all of the respondents stated that the biggest challenge that they faced during simulative learning practice was anxiety and stress. Cooperation within the teamwork and time management also became the barriers for them to perform well at the time of simulation. A debriefing session after simulation played an important role to know the mistakes and reflect back their actions. Absolutely, simulative learning practice is important for nursing students and many studies proved that there are many benefits to students regarding competency skills due to this type of learning.